Ginger Cultivation and Use - Kaushik, Prashant; Shabir Ahmad, Rabia (IntechOpen, 2023)
Zingiber officinale, often referred to as ginger, is the scientific name for the blooming plant-producing underground rhizome. The rhizome may be used both in the kitchen and in traditional forms of healing. It is a herbaceous perennial that may survive for many years and generates annual pseudostems (false stems made of the coiled bases of leaves) that reach heights of around one meter, and bare, thin leaf blades. Antioxidants and bioactive compounds are present in ginger. This book explores recent developments in ginger production and biochemical research against the background of current and impending environmental change.